Pendidikan Nilai: Telaah tentang Model Pembelajaran - Subur Subur (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
A nation that praises Divine value, progress, and humanity will always sensitive about value issue. Value become reference and parameter each time human think, stand, and act. It because value is important aspect of civilized human life. Values will always being sought, obeyed, and acted; even not every man can practice it perfectly, especially in this materialistic and hedonistic era. Value internalisation will become harder. However, changing behaviour and life tendency that producing much clash and conflict causing human awareness about importance of value. Here, value can be developed through many models according to human character.